Engineering of stepwise-targeting chitosan oligosaccharide conjugate for the treatment of acute kidney injury. (15th March 2021) - Wang, Dong-Wei; Li, Shu-Juan; Tan, Xue-Ying; Wang, Jin-Hui; Hu, Ying; Tan, Zeng; Liang, Jing; Hu, Jing-Bo; Li, Yan-Guo; Zhao, Yu-Fen
Graphical abstract: Schematic illustration of triphenyl phosphine-low molecular weight chitosan-curcumin (TPP-LMWC-CUR, TLC) conjugate for the treatment of acute kidney injury. TLC is specifically internalized by renal tubular epithelial cells via Megalin-mediated endocytosis, and then preferentially distributed in the mitochondria. The increased accumulation of CUR in the mitochondria effectively removes excessive reactive oxygen species and attenuates oxidative stress damage during suffering acute kidney injury. Highlights: We successfully developed stepwise-targeting chitosan oligosaccharide conjugate, TLC. TLC is specifically internalized by the renal tubular epithelium cells, and then preferentially distributed in mitochondria. TLC treatment effectively reduce ROS level, and then improve renal functions. Abstract: Acute kidney injury (AKI) is a common and serious clinical syndrome of acute renal dysfunction in a short period. One of therapeutic interventions for AKI is to reduce ROS massively generated in the mitochondria and then ameliorate cell damage and apoptosis induced by oxidative stress. In this study, stepwise-targeting chitosan oligosaccharide, triphenyl phosphine-low molecular weight chitosan-curcumin (TPP-LMWC-CUR, TLC), was constructed for sepsis-induced AKI via removing excessive ROS in renal tubular epithelial cells. Benefiting from good water solubility and low molecular weight, TLC was rapidly and preferentially distributed in the renal tissues and then specifically internalized by tubular epithelium cells via interaction between Megalin receptor and LMWC. The intracellular TLC could further delivery CUR to mitochondria due to high buffering capacity of LMWC and delocalized positive charges of TPP. Both in vitro and in vivo pharmacodynamic results demonstrated the enhanced therapeutic effect of TLC in the treatment of AKI.